Penerapan Prinsip Murabahah Sebagai Keunggulan Kompetitif Dan Strategi Unit Bisnis Baru Bank Konvensional - Peter . (Jurnal Manajemen Maranatha, 2010)
Murabahah is one from many principal in Syariah Banking, Murabahah can applied in Syariah Banking System, and also at conventional bank. Murabahah giving more benefit for bank and customer. If we see from the bank side, we will find that will be a new marketing competitive strategy to get a new line for funding. At the other side, customer will get a cheaper financing and a certainty price than using a conventional financing. Murabahah gives more advantage if we compare to flat rate and effective rate financing, because Murabahah not applying interest but using profit margin which it show as transparency management to the customer.Keywords: Murabahah, Syariah banking, Conventional, Competitive Strategy.